Improving Learning Engagement through the Implementation of Problem-Based Learning (PBL) Model with a Culturally Responsive Teaching (CRT) Approach and Homogeneous Group Discussions - Hidayati, Maulidiana; Junaidi, Eka; Martini, Hasinah (Lombok Institute, 2024)
This classroom action research aims to enhance the learning engagement of Grade XII students at SMA Negeri 2 Mataram in studying colligative properties of solutions through the implementation of the Problem-Based Learning (PBL) model, using a Culturally Responsive Teaching (CRT) approach and homogeneous group discussions. The classroom action research was conducted in two cycles. The increase in student engagement was assessed based on changes in student groupings, categorized into Groups 1, 2, 3, and 4. Group 1 represented students with high learning engagement. Before the intervention, 28% or 12 students were in Group 1, which increased to 42% or 15 students by the end of Cycle II. Additionally, no students remained in Group 4, representing those with very low engagement. Homogeneous group discussions fostered increased learning engagement by allowing the teacher to create an environment more responsive to each student's needs. The problem-based learning model combined with the Culturally Responsive Teaching (CRT) approach successfully enhanced student engagement, as the problems presented in learning activities were aligned with real-life situations experienced by the students in their daily lives.